Creating Public Awareness of How Goats Are Reared and Milk Produced May Affect Consumer Acceptability. Issue 3 (2nd July 2016) - Musto, Mauro; Cardinale, Daniele; Lucia, Pietro; Faraone, Daniela
Abstract : This study evaluated whether showing a video of the different ways of raising goats for milk affected consumer acceptability. Four combinations, 2 Videos (intensive [INT] and semiextensive [SEM] system) × 2 Milk Types (semiskimmed [S] and whole [W] milk), were evaluated by 70 habitual consumers of goat milk, who scored their liking and purchase intention during blind ( B ), expected ( E ), and informed ( I ) acceptability sessions. In the B session, consumers tasted both milk types without information. S samples were preferred over W samples. In the E session, SEM video created high expectations in terms of milk liking and purchase intent, whereas the opposite happened when showing INT video. In the I session, consumers showed a clear preference for combinations created using SEM video, regardless of milk type. W-SEM and S-INT were worse (negative disconfirmation) and better (positive disconfirmation) than expected, respectively. A complete assimilation toward expectations occurred only for S-INT. INT video adversely affected the acceptability of S samples. Concerning purchase intent, W-SEM and S-SEM were worse than expected, but the assimilation was complete only for S-SEM: SEM video increased purchase intent for S samples.